The development of a multidimensional Consumer Perceived Value scale in ophthalmology services - Gheorghe, Consuela-Mădălina (Rom J Ophthalmol, 2019)
Objective: The aim of this study was to investigate the dimensionality of Consumer Perceived value in Romanian ophthalmology services. Material and Methods: The sample consisted of 173 consumers of private ophthalmology services, recruited using a systematic method. The design of the study was cross-sectional and the research instrument was a self-administered questionnaire, namely a Consumer Perceived Value Scale, developed by Chahal and Kumari. The dimensions of the Consumer Perceived Value were assessed by conducting an Exploratory Factor Analysis and the scale’s reliability was checked with the Cronbach’s alpha coefficient. Results: The findings of the Exploratory Factor Analysis revealed that all initial factors loaded properly and the Cronbach’s alpha coefficients had values greater than the recommended threshold of 0.70. As such, the Consumer Perceived Value scale had a Cronbach’s alpha coefficient of 0.77 and encompassed the following dimensions: transaction value, aesthetic value, efficiency value, self-gratification value, acquisition value and social interaction value. Conclusions: Applying efficient value strategies in ophthalmology services may ensure consumer satisfaction, loyalty, positive word-of-mouth and offer competitive advantages.